Molecular and functional characterization of the American cockroach, Periplaneta americana, Rab5: the first exopterygotan low molecular weight ovarian GTPase during oogenesis. (8th August 2017) - Elmogy, Mohamed; Mohamed, Amr A.; Tufail, Muhammad; Uno, Tomohide; Takeda, Makio
Abstract: The small Rab GTPases are key regulators of membrane vesicle trafficking. Ovaries of Periplaneta americana (Linnaeus) (Blattodea: Blattidae) have small molecular weight GTP/ATP‐binding proteins during early and late vitellogenic periods of oogenesis. However, the identification and characterization of the detected proteins have not been yet reported. Herein, we cloned a cDNA encoding Rab5 from the American cockroach, P. americana, ovaries ( PamRab5 ). It comprises 796 bp, encoding a protein of 213 amino acid residues with a predicted molecular weight of 23.5 kDa. PamRab5 exists as a single‐copy gene in the P. americana genome, as revealed by Southern blot analysis. An approximate 2.6 kb ovarian mRNA was transcribed especially at high levels in the previtellogenic ovaries, detected by Northern blot analysis. The muscle and head tissues also showed high levels of PamRab5 transcript. PamRab5 protein was localized, via immunofluorescence labeling, to germline‐derived cells of the oocytes, very early during oocyte differentiation. Immunoblotting detected a ∼25 kDa signal as a membrane‐associated form revealed after application of detergent in the extraction buffer, and 23 kDa as a cytosolic form consistent with the predicted molecular weight from amino acid sequence in different tissues including ovary, muscles and head. The PamRab5 during late vitellogenic periods is required to regulate the endocytotic machinery during oogenesis in this cockroach. This is the first report on Rab5 from a hemimetabolan, and presents an inaugural step in probing the molecular premises of insect oocyte endocytotic trafficking important for oogenesis and embryonic development.